The Role of Quality Management in Improving Educational Outcomes and Developing Critical Thinking in Libyan Society: An Analytical Study in Light of Deming, Juran, and Kaizen Models (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the role of quality management in improving educational outcomes and developing critical thinking in Libyan society through the application of Total Quality Management frameworks, particularly the contributions of Deming, Juran, and Kaizen philosophy of continuous improvement. The study adopted a descriptive analytical approach based on reviewing relevant literature and previous studies. Findings revealed that quality management contributes to improving institutional efficiency, enhancing educational outcomes, and fostering learning environments that support critical thinking. The study also found that weak implementation of quality systems in some Libyan educational institutions limits the full utilization of educational capacities. The study recommended adopting modern quality systems, integrating critical thinking skills into curricula, and activating continuous improvement practices within Libyan educational institutions.
Keywords: Quality Management, Educational Outcomes, Critical Thinking, Kaizen, Higher Education.